Європейський вектор розвитку бізнес-адміністрування на підприємстві на основі теорії обмежених систем - Маковоз, Оксана Сергіївна; Яценко, Ольга Миколаївна; Задесенець, Дмитро В. (ПУ "Причорноморський науково-дослідний інститут економіки та інновацій", 2020)
У статті досліджено та охарактеризовано особливості сучасного вектору розвитку бізнес-адміністрування на підприємстві на основі теорії обмежених систем. Автори, у ході дослідження, дійшли висновку, що бізнес-адміністрування повинно забезпечувати координацію діяльності та синхронність виконання всіх робіт в системі управління сучасним підприємством. Розглянуто теорію обмежених систем щодо побудови ефективної системи бізнес-адміністрування на підприємстві, яке має базуватися на принципах процесного підходу, стратегії планування ресурсів, ощадливого виробництва та сертифікації систем управління підприємств за стандартами ISO. Охарактеризовано сутність теорії ТОС у бізнес-адмініструванні, яка полягає у виявленні обмеженості бізнес-системи, підпорядкуванні усієї роботи підприємства особливостям і потребам вузького місця, усуненні його і пошуку чергового обмеження для подальшого удосконалення системи.

In article it is investigated and it is characterized features of a modern vector of development of business administration at the enterprise on the basis of the theory of limited systems. Authors during the research came to a conclusion that business administrations has to provide coordination of activity and synchronism of performance of all works in a control system of the modern enterprise. The control system is understood as a system which influence is directed to object of management with its simultaneous transformation in wished a state according to certain quantitative and qualitative parameters and also which consists of elements that the functioning united by a common goal. At the same time productive activity of the enterprise can be provided due to introduction of a system of administrative management which is intended to simplify management process, raising quality indicators of work that allows without essential investments in modernization of production to reduce product cost, to liquidate a shortcoming and to provide long-term competitiveness. At the present stage of development of economy of Ukraine when the enterprises function in the conditions of aggravation of the crisis phenomena and geoeconomic instability, big the value gets introductions of rational and effective forms and methods of management of the enterprise. The relevance of a research is that today the value of business administration constantly grows as in modern conditions of managing the corresponding approaches to the solution of problems of increase in effectiveness of activity of the enterprises and the detailed epresentation of essence and forms of management processes taking into account limitation of resources are necessary. It is considered the theory of TOС on creation of an effective system of business adminis tration at the enterprise which has to be based on the principles of process approach, strategy of planning of resources, careful production and certification of control systems of the enterprises for the ISO standards. The essence of the theory of TOС in business administrations which consists in identification of limitation of a business system, submission of all work of the enterprise to features and requirements of a bottleneck, its elimination and search of the next restriction for further improvement of a system is characterized.
The european vector of development of business administration at the enterprise because of the theory of limited systems
Keywords: менеджмент; адміністративний менеджмент; система управління підприємством; бізнес; бізнес-адміністрування; теорія обмежень